Celebrating successes: A year of NEXUS Gains - McCartney, Matthew P.; Ringler, Claudia (CGIAR System Organization, 2023)
As the CGIAR Initiative on NEXUS Gains completes its first successful year the team has been reflecting on progress and next steps. In all basins we have created strong relationships with decision makers and stakeholders across the water, energy, food and environment nexus. We have worked with these groups to develop tools, such as the Nexus Capacity Scorecard below, which can support them to apply a systems approach, minimizing trade-offs and maximizing synergies in natural resources management.